Upgrading low quality natural gas with Co2 selective polymers membrane - Meor Mohd Dhiya, Mior Zahidi (2009)
The aim of this research is to determine the most suitable polymer membrane between polyvinylidene fluoride (PVDF), Polyacrylonitrile (PAN) and hybrid polymer membrane of polysulfone (PSU) and polyethersulfone (PES) for separating CO2 from crude natural gas. These polymers are mixed with suitable solvent in order to create polymeric solution. Flat sheet membranes were developed from this polymeric solution using standard method. Flat sheet membranes are then introduced to the separation process using permeability unit to study permeability and selectivity of each membrane. The test was carried out by using three gas inlet volumetric flow rate, 0.1, 0.2 and 0.3 L/min at 0.5, 1.0 and 1.5 Bar. The test gas used was CO2 and CH4 gas, both have purity over 99%. Standard soap bubble method was used to determine permeate gas flow rate. Results shows, PVDF membrane are determined as the suitable membrane for the separation process because PVDF membrane has low CO2 selectivity and high permeability of CH4 compare to the other polymers membrane. It is also discovered that by increasing gas inlet flow rate, permeability of the gas also increase and selectivity is inversely proportional to permeability. In order to improve in the next study, other parameter such as coating the membranes need to be considered as well.